Clustering Analysis on Ottoman Waqf Studies - Rusydiana, Aam Slamet; Lila, Nazan (Journal of Islamic Economics Literatures, 2025)
This article aims to scan and classify Ottoman waqf studies by cluster analysis method, and fill the gap in the literature. In addition, this study is expected to be a guiding resource for those who want to do research on Ottoman waqfs.In the study, Scopus database was scanned using the keywords "Ottoman AND waqf" and the data obtained were analyzed by clustering method. The screening was conducted on May 9, 2024. As a result of the screening, a total of 137 studies were identified, including 106 journal articles, 2 books, 11 book chapters, 3 conference papers and 15 review articles. The date range of all studies is between 1979 and 2024. Then, the collected data was processed and analyzed with the R-Biblioshiny software program. This program is a free open source that provides tool support for bibliometric analysis research. The biggest feature of this software is that it creates bibliometric maps using the metadata of the collected articles. In addition to the R-Biblioshiny software program, the Scopus AI was also used to strengthen the analysis. Scopus AI is an AI-powered platform designed to navigate over the Scopus database. As a result of the cluster analysis, 3 main findings were reached. The first of these findings is the significance of the Egyptian region in the studies on Ottoman waqfs. The second finding is the richness of the cluster that touches on the function and importance of Ottoman waqfs throughout the centuries. The third important finding is the size of the cluster, which is generally categorized under the heading of "Ottoman waqfs". Ottoman waqf system included dynastic waqfs established by sultans and high-ranking state officials, with large budgets and providing various public services. Thus, these large waqfs had an economic impact known as the waqf economy.